Creative Activity of Students Through Interdisciplinary Integration in Primary Education - Achilov Ogabek Narzullaevich (Genius Publishing Group, 2024)
In the article are disclosed some conditions of integrated lessons arrangement in primary education. As well there are expressed apparent characteristics of property integrated lessons. Also, on the assumption of integrated lesson, author determined structure of given type lessons. Presented visions for that matter, reflected on example of jobs training lessons
Keywords: primary education; structure integration lesson; training lessons